Policy Challenges of Indonesia’s Local Content Requirements on Power Generation and Turbine Production Capability - Sitompul, Rislima Febriani; Endri, Endri; Hasibuan, Sawarni; Jaqin, Choesnul; Indrasari, Arum; Putriyana, Lia (International Journal of Energy Economics and Policy, 2022)
The demand for electricity in Indonesia will continue to increase. Thus, the market opportunity for the power generation industry needs to be optimally utilized by domestic business actors through the Local Content Requirements (LCR) policy. Through exploratory techniques, the primary goal of this research is to assess the capability of Indonesia’s national turbine industries and research institutions, as well as to develop policy recommendations for maximizing the use of local content in order to comply with the Ministry of Industry’s Domestic Component Level Regulation, also known as Local Content Requirements (LCR). There are at least three challenges that need attention, namely technology capability and efforts, infrastructure, and institution. Although Indonesia has good prospects and opportunities to develop large-scale turbines, the challenges ahead in developing coal-fired turbines will be more complex due to the strengthening of the clean development paradigm. Thus, it is important to rethink the direction of developing LCR policies for coal-fired turbines. The study recommended budget allocation for ensuring continuity of turbine prototyping, simplify the process to obtain technology licensing, and developing industries that can support materials for turbine industries.